Valuing Public Goods: The Life Satisfaction Approach - Bruno S. Frey; Simon Luechinger; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2004)
This paper discusses a novel approach to elicit people's preferences for public goods, namely the life satisfaction approach. Reported subjective well-being data are used to directly evaluate utility consequences of public goods. The strengths of this approach are compared to traditional approaches and identification issues are addressed. Moreover, it is applied to estimate utility losses caused by terrorist activities in France, the UK and the Republic of Ireland. Terrorism in these countries depresses life satisfaction in a sizeable and robust way. However, the calculation of the trade-off between terrorism and income requires improved measurement of the marginal utility of income.
Keywords: D61; D74; H41; H56; I31; 330; life satisfaction approach; non-market valuation; cost-benefit analysis; subjective well-being; and terrorism